Plastic neuroscience: studying what the brain cares about - Dumit, Joseph (Frontiers in Human Neuroscience, 2014)
Drawing on Allan Newell’s “You can’t play 20 questions with nature and win,” this article proposes that neuroscience needs to go beyond binary hypothesis testing and design experiments that follow what neurons care about. Examples from Lettvin et. al. are used to demonstrate that one can experimentally play with neurons and generate surprising results. In this manner, brains are not confused with persons, rather, persons are understood to do things with their brains.